Evaluation of Mechanical Strength and Non-Destructive Characteristics of Self Compacted Concrete Incorporating Coir Pith Ash - Amandeep Sehrawat (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Self Compacted Concrete (SCC) has emerged as foremost effective advancements in concrete technology, primarily due to its ability to achieve full compaction without the need for external vibration. Its high paste content, optimized flow behavior, and controlled aggregate gradation make it distinct from conventional concrete. However, these same characteristics can influence how non-destructive testing (NDT) methods perform when used to estimate mechanical strength. In the present study, SCC was produced using Ordinary Portland cement (OPC 53 grade) blended with ground granulated blast furnace slag (GGBS), FA, and coir pith ash as supplementary cementitious materials. A polycarboxylate-based superplasticizer was added to achieve the required self-compaction. The concrete’s strength development was evaluated using ultrasonic pulse velocity (UPV) testing, while splitting tensile behavior was studied through prism testing to establish correlations with UPV readings. All specimens were cast from a single batch and cured under standard conditions. The compressive strength values ranged between 48.32 MPa and 91.56 MPa, while the UPV values varied from 4.12 km/s to 5.08 km/s. The statistical analysis showed a strong correlation (R² = 0.97) between UPV and compressive strength, confirming the reliability of UPV for predicting the mechanical performance of SCC. Overall, the study demonstrates that UPV testing can be effectively used to estimate the in-situ strength of SCC containing sustainable pozzolanic materials, offering a practical, non-destructive alternative for strength evaluation and quality assurance in modern concrete construction.